Hubungan Pengetahuan Dan Sikap Wanita Usia Subur Dengan Deteksi Dini Kanker Leher Rahim Metode IVA di Desa Soahuku Kecamatan Amahai Tahun 2022 - Yuliana Yuliana; Andi Herliah (Jurnal Nurse, 2023)
Ca Cervix at the fourth rank from all of oncology in women in the word after ca mamae, colorectum and lungs. Early detection use IVA method. Data from Amahai community health center in 2019 from 386 women in fertile age who have ca cervic detection as much as 73 women (19%). In 2020, from 401 women in fertile age only 97 women (24%) have early detection. In 2021, from 390 women in fertile age who have early detection amounted 60 women (15%). This research determine to relationship knowledge and attitude women in fertile age with ca cervic early detection with IVA method inn Amahai subdistrict Soahuku village. This research used analysis description with cross sectional study. 78 women in fertile age as respondent of this research. Instrument of this research used questionnaire. Data processing used SPSS with chi square test. Result of chi square got relationship knowledge of women in fertile age with early detection equal 0,000 p<0,05). Conclution of this research showed there was relattionsgip between knowledge and attitude of women in fertile age to ca cervix early detection with IVA method in, Amahai subdistrict, Soahuku village.